Profile simulation software for trigonometric and polynomial cams design (2007)
This paper discusses the development of unique software for the design of various cam profiles for the plate cam operating a flat face follower. The method employed in this work is that of generating geometrical cam coordinates using standard cam motions, thereby avoiding the problem of undercutting resulting from graphical layout methds for similar cam and follower types. Determination of critical design output parameters were carried out by the developed software computational algorigthm. The software was validated by using it to simulate a number of standard cases. For the standard case having the follower profile Dwell(200o)-Rise (280o)-Dwell(300o)-Return(360o)and performing cycloid rise and return motion, the prime circle radius for the cam profile and face width of the follower were calculated as 55.72mm and 33.76mm while the maximum and minimum follower velocities were 13.70mm/rad and -10.27mm/rad respectively. These values, as well as those obtained for other standard cases simulated, were found to be in agreement with earlier works done in this area of research